Analisis Kesulitan Guru Dalam Pelaksanaan Pembelajaran Matematika Kelas IV di Phatna Witya Yala School Thailand - Muhammad Ijlal Faza Antarista; Veryliana Purnamasari; Filia Prima Artharina (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this research is to analyze the difficulties encountered by teachers in implementing mathematical learning in the 4th grade of Phatna Witya Yala School Thailand. Research using qualitative methods with a type of qualitatively descriptive research, the subject on this research is a 4th grade mathematics teacher. Data is collected through in-depth interviews, collection of research documentation and learning observations which are then analyzed descriptively. The results of this study showed that 4th grade mathematics teachers experienced some difficulties such as conditioning non-conducive classes, determining learning methods that match the characteristics and needs of students, as well as accommodating differences in student abilities. Teachers were able to overcome a variety of such problems, including applying a reward point system, observing student characteristics before determining methods of learning, and providing individual support to students who lag behind. The research concludes the need for improved teacher competence and school support to optimize mathematics learning in the 4th grade at Phatna Witya Yala School Thailand.